Complete mitochondrial genome of the jellyfish, Chrysaora quinquecirrha (Cnidaria, Scyphozoa). (February 2014) - Hwang, Dae-Sik; Park, Eunji; Won, Yong-Jin; Lee, Woo-Jin; Shin, Kyoungsoon; Lee, Jae-Seong
Abstract We sequenced 16, 775 bp of the linear mitochondrial DNA of the jellyfish Chrysaora quinquecirrha and characterized them. C. quinquecirrha has 13 protein-coding genes (PCGs), 16S rRNA and 12S rRNA with 3 tRNAs (tRNA-Leu, tRNA-Ser(TGA), tRNA-Met) as shown in Aurelia sp. nov. Both have another two PCGs such as helicase and orf363 with telomeres at both ends. The PCGs of C. quinquecirrha shows anti-G bias on 2nd and 3rd positions of PCGs as well as anti-C bias on 1st and 3rd positions of PCGs.